SPE European Formation Damage Conference 1997
DOI: 10.2118/38154-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Recommended Practice for Formation Damage Testing

Abstract: Well productivity can be significantly affected by damage to the near well-bore area caused during drilling in the reservoir section of a well. Historically, the use of perforated completions allowed for penetration of the producing formation beyond the damaged area but the recent trend towards non-perforated completions has resulted in an increased emphasis on damage minimisation. This, in turn, has increased the importance of evaluating drilling fluids and completion techniques used from a reservoir damage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, Marshall et al (1997 concludes that return permeability measurement is one of the most common evaluation tools used for selecting an RDF system. Attempts to standardize, establish repeatability or reproducibility, and improve return permeability testing are also well documented (Marshall et al 1997;Marshall et al 1999;Byrne et al 2011). Han et al (2005) presents a means to bridge the gap between the laboratory-measured data and field skin factors while focusing on laboratory-measured fluid loss.…”
Section: Basic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Marshall et al (1997 concludes that return permeability measurement is one of the most common evaluation tools used for selecting an RDF system. Attempts to standardize, establish repeatability or reproducibility, and improve return permeability testing are also well documented (Marshall et al 1997;Marshall et al 1999;Byrne et al 2011). Han et al (2005) presents a means to bridge the gap between the laboratory-measured data and field skin factors while focusing on laboratory-measured fluid loss.…”
Section: Basic Methodsmentioning
confidence: 99%
“…There are two methods documented in the literature to flow back through the core after filtercake deposition (Marshall 1997(Marshall , 1999. The first method advocates using constant flow rate and there are disadvantages with this method although it is simplistic and readily performed by most return permeability apparatus.…”
Section: Recommended Test Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of studies and equipment specifications are used to examine areas such as drilling, completion, production, injection, workover, stimulation, and sanding. Comparisons of laboratories have shown that the results are susceptible to variations in test equipment, procedure, and conditions (Marshall et al, 1997;Byrne and Patey, 2007). Formation damage laboratory studies aid in risk-reduction when making important well design decisions, so reducing uncertainty surrounding test results will make the testing itself more useful and valuable.…”
Section: Introductionmentioning
confidence: 99%